2009
DOI: 10.1016/j.juro.2009.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of a Genitourinary Skills Training Curriculum for Medical Students

Abstract: An intensive skills training curriculum significantly improved medical student comfort and knowledge with regard to basic genitourinary skills including testicular examination, rectal examination, and Foley catheter placement in the male and female patient. Further followup will be performed to determine the application of these skills during clinical clerkship rotations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…This seems surprising given that there are a variety of methodological teaching approaches to deliver DRE skills, such as training on part-task trainers [ 11 ], finger movement simulators including video feedback [ 12 , 13 ], rectal and urological teaching associates (RTA; UTA; specially trained laypersons to assist in DRE or even serve as a probands for practice) [ 11 , 14 ] and standardized patients [ 15 - 17 ]. Although simulators show high validity [ 18 , 19 ] and lead to reduced inhibition and fear with regard to DRE [ 20 ], standardized patients are regarded as one of the most useful methods to deliver DRE skills [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This seems surprising given that there are a variety of methodological teaching approaches to deliver DRE skills, such as training on part-task trainers [ 11 ], finger movement simulators including video feedback [ 12 , 13 ], rectal and urological teaching associates (RTA; UTA; specially trained laypersons to assist in DRE or even serve as a probands for practice) [ 11 , 14 ] and standardized patients [ 15 - 17 ]. Although simulators show high validity [ 18 , 19 ] and lead to reduced inhibition and fear with regard to DRE [ 20 ], standardized patients are regarded as one of the most useful methods to deliver DRE skills [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar multipart survey study conducted by the Department of Urology at our institution has demonstrated very encouraging results 7. Second‐year UC Irvine medical students, upon completing a mandatory 5.5‐hour genitourinary skills (i.e., Foley catheter placement, suturing and knot tying, digital rectal exam) training session, reported greater overall knowledge and comfort with performing elements of the genitourinary exam.…”
Section: Introductionmentioning
confidence: 77%
“…Ninety‐five (94.1%) and 77 (76.2%) medical students completed pre‐ and postsurveys, respectively. Mean Likert rating scores were compared between pre‐ and postsurveys similar to Kaplan et al using an unpaired Student's t ‐test with a significance level of 0.05 7. The results of students' comfort level ratings are summarized in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Students frequently fail to acquire such skills owing to lack of resources or fear of harming the patients or they may not attend urology classes at all. [7][8][9] Therefore, easier and novel approaches to epididymis examination have been introduced, albeit still insufficient. This is because these approaches are not fully applied in anterior epididymis positions and examinations are carried out when the patients are supine.…”
Section: Discussionmentioning
confidence: 99%